2022
DOI: 10.1002/mp.15901
|View full text |Cite
|
Sign up to set email alerts
|

Computer‐aided diagnostic models to classify lymph node metastasis and lymphoma involvement in enlarged cervical lymph nodes using PET/CT

Abstract: Background It is a clinical problem to identify histological component in enlarged cervical lymph nodes, particularly in differentiation between lymph node metastasis and lymphoma involvement. Purpose To construct two kinds of deep learning (DL)‐based computer‐aided diagnosis (CAD) systems including DL‐convolutional neural networks (DL‐CNN) and DL‐machine learning for pathological diagnosis of cervical lymph nodes by positron emission tomography (PET)/computed tomography (CT) images. Methods We collected CT, P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 48 publications
0
15
0
Order By: Relevance
“…Our findings suggest that the performance of the DL model may be affected when applied across different PET cameras, and the difference in performance may be attributed to the differences between the characteristics of digital and analog PET scanners. Another possibility is that the DL model likely performs better in the training cohort than in the testing cohort [38]. Therefore, this may be another explanation for the difference of DL model performance between analog and digital PET cohorts.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Our findings suggest that the performance of the DL model may be affected when applied across different PET cameras, and the difference in performance may be attributed to the differences between the characteristics of digital and analog PET scanners. Another possibility is that the DL model likely performs better in the training cohort than in the testing cohort [38]. Therefore, this may be another explanation for the difference of DL model performance between analog and digital PET cohorts.…”
Section: Discussionmentioning
confidence: 99%
“…The output of the last block connects to a sigmoid function layer to generate the prediction [38]. ResNet-50 exhibited the best diagnostic performance in classifying lymph node metastasis among different DL-CNN architectures [38]. During the training step, random rotation (−45° to 45°), reflection (x- and y- direction), and scaling (0.9 to 1.1) were applied to the images to avoid overfitting.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Further, the authors showed that the constructed ML model with the RF algorithm had good performance in differentiating malignant lymphoma and sarcoidosis, with an AUC of 0.94. Yang et al [ 79 ] revealed that the ML model with the SVM algorithm constructed according to combined CNN-based features and PET-radiomics had a great potential in distinguishing malignant lymphoma from enlarged metastatic cervical lymph nodes (AUC: 0.948).…”
Section: Clinical Application Of 18 F-fdg Pet/ct R...mentioning
confidence: 99%
“…AUC: 0.94 2. AUC: 0.95 Yang et al [ 79 ] 2023 Cervical lymph node Malignant lymphoma vs. metastasis n = 165 CNN model Combined PET radiomics-based + CNN-based model alone SVM Combined model Training and validation cohorts AUC: 0.948 Cui et al [ 80 ] 2023 Brain tumor Malignant lymphoma vs. metastasis n = 51 PET radiomics-based model alone RF Training and validation cohorts AUC: 0.93 Predicting treatment response or survival Frood et al [ 84 ] 2022 DLBCL Recurrence after chemotherapy n = 229 Combined clinical + PET radiomics-based model alone Ridge regression Training and validation cohorts AUC: 0.73 Cui et al [ 85 ] 2022 DLBCL PFS after chemotherapy n = 271 Clinical model PET radiomics-based model Combined clinical + PET radiomics-based model alone RF + cox proportional hazard Combined model Training and validation cohorts C-index: 0.853 Frood et al [ 86 ] 2022 HD Recurrence after chemotherapy or RT n = 289 Combined clinical + PET radiomics-based model alone …”
Section: Clinical Application Of 18 F-fdg Pet/ct R...mentioning
confidence: 99%